Responder
Here are the factored forms of the given quadratic expressions:
1. \( x^{2} - 6x + 5 = (x - 1)(x - 5) \)
2. \( x^{2} - 5x + 6 = (x - 2)(x - 3) \)
3. \( x^{2} - 5x - 6 = (x - 6)(x + 1) \)
4. \( x^{2} - x - 6 = (x - 3)(x + 2) \)
Solución
Certainly! Let's factor each of the given quadratic expressions.
### 3) \( x^{2} - 6x + 5 \)
**Objective:** Factor the quadratic expression.
**Method:**
1. Look for two numbers that multiply to **+5** (the constant term) and add up to **-6** (the coefficient of \( x \)).
2. The numbers are **-1** and **-5** because:
- \((-1) \times (-5) = +5\)
- \((-1) + (-5) = -6\)
**Factored Form:**
\[ x^{2} - 6x + 5 = (x - 1)(x - 5) \]
---
### 4) \( x^{2} - 5x + 6 \)
**Objective:** Factor the quadratic expression.
**Method:**
1. Look for two numbers that multiply to **+6** and add up to **-5**.
2. The numbers are **-2** and **-3** because:
- \((-2) \times (-3) = +6\)
- \((-2) + (-3) = -5\)
**Factored Form:**
\[ x^{2} - 5x + 6 = (x - 2)(x - 3) \]
---
### 5) \( x^{2} - 5x - 6 \)
**Objective:** Factor the quadratic expression.
**Method:**
1. Look for two numbers that multiply to **-6** and add up to **-5**.
2. The numbers are **-6** and **+1** because:
- \((-6) \times (+1) = -6\)
- \((-6) + (+1) = -5\)
**Factored Form:**
\[ x^{2} - 5x - 6 = (x - 6)(x + 1) \]
---
### 6) \( x^{2} - x - 6 \)
**Objective:** Factor the quadratic expression.
**Method:**
1. Look for two numbers that multiply to **-6** and add up to **-1**.
2. The numbers are **-3** and **+2** because:
- \((-3) \times (+2) = -6\)
- \((-3) + (+2) = -1\)
**Factored Form:**
\[ x^{2} - x - 6 = (x - 3)(x + 2) \]
---
**Summary of Factored Forms:**
1. \( x^{2} - 6x + 5 = (x - 1)(x - 5) \)
2. \( x^{2} - 5x + 6 = (x - 2)(x - 3) \)
3. \( x^{2} - 5x - 6 = (x - 6)(x + 1) \)
4. \( x^{2} - x - 6 = (x - 3)(x + 2) \)
If you need further assistance or have more questions, feel free to ask!
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución